Pemeliharaan Hubungan dan Komunikasi Organisasi via Media Siber - Sanjaya, Andika; Irwansyah,; Alunaza, Hardi (Jurnal ILMU KOMUNIKASI, 2017)
In the context of an organization, the public may have various interests. The practitioners of public relations need the right formula to maintain the relationship with their public. This research intends to find and evaluate the proper typology to be implemented into the Cyber PR context. This research uses descriptive and comparative content analysis methods. An organization can maintain their publics by doing entertainment, direct communication, two-way communication, and humor. This research amplifies that the current typology can be implemented in the context of Cyber PR, although it receives criticism.Â